(untitled) (Bangladesh Pharmaceutical Journal, 2018)
Investigations were performed to find out new microbial enzymes as thrombolytics having better efficacy and specificity. Mutant strain of Bacillus species, B. licheniformis MZK05M9 was cultured in modified urea-glucose media followed by purification using ammonium sulphate precipitation and ultrafiltration through centricon tube of specific MWCO value. The production method yielded 823.42 units/mg of the crude enzyme from mutant strain MZK05M9 and after purification 37695.64 units/mg. The molecular weight of the purified enzyme was estimated as 27.2 kDa and purification increased its specific activity to 16.5 fold with a recovery of 10%. The purified proteases were identified as serine proteases by irreversible inhibition of activity with phenylmethylsulfonyl fluoride (PMSF) and it exhibited 32.84% thrombolytic activity, by in vitro clot lysis assay. Stability studies showed that crude enzyme from mutant strain MZK05M9 remained stable up to a temperature of 45˚C and showed maximum stability at pH range 7.5 to 8.5. Our observation indicates that proteases produced by Bacillus licheniformis mutant have the potential to be developed as a viable thrombolytic agent. Bangladesh Pharmaceutical Journal 21(1): 63-70, 2018